Respuesta :

Answer:

The answer to your question is:

x = 2

y = 6

Step-by-step explanation:

3x -  y  =  0       (1)

5x + 2y = 22      (2)

Solve by substitution

from (1)          3x = y

then      5x + 2(3x) = 22                              y = 3x

             5x + 6x = 22                                  y = 3(2)

             11x = 22                                         y = 6

              x = 22/11

              x = 2            

Matrix

Δ       3    -1

         5    2          =    6 + 5 = 11

Δx =  0   -1

      22     2            =    0 + 22 = 22

Δy       3     0

          5     22        =    66 - 0 = 66

x = Δx / Δ = 22 / 11 = 2

y = Δy / Δ = 66 / 11 = 6

ACCESS MORE